Respon Beberapa Genotip Kacang Tunggak (Vigna unguiculata L.) terhadap Cekaman Salinitas - Eritria Ulina Absari; Kuswanto Kuswanto (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2019)
Salinity stress in plants still an important problem in agriculture throughout the world. Salinity makes plants unable to grow and produce well. Cowpea is one of the legume plants that is tolerant of drought and acidity so that it is prospectively developed on land such as dry land and acid soils. The purpose of this study was to determine cowpea genotypes that showed the most tolerant response to salinity and to know the interaction of genotypes and salinity. The tools used in the study were stationery,shovels,buckets,dipper,rulers,analytical scales,camera, pots, portable EC meters,chlorophyll meters. The materials used in the study were the seeds of ten cowpea genotypes (MLG 17013, MLG 17019,MLG17027,MLG17042,MLG17051,MLG17055,MLG17057,MLG17060,KT-4,KT-5),soil,water,fertilizer,urea,TSPfertilizer,KCL fertilizer, manure, NaCl and labels. This study using slit plot design with 3 replications. The mainplot is EC soil at 4 dS/m and 8 dS/m and nonstress. The subplot is 10 genotypes of cowpea. The study was carried out in a greenhouse of the Various Peanut and Tuberculosis Research Institute,Malang Regency,East Java. The research was conducted from March to June 2018. The results of the study were that salinity affected the decrease in germination percentage,plant height, number of branches, chlorophyll index,weight of pod/plant, number of pods/plants,length of pods/plants, weight of 100 seeds,weight of planting seeds,age of flowering and age of harvesting. The conclusions from the study were that the 3 most tolerant genotypes based on stress tolerance index (ITC) and based on scoring of cowpea plants showed tolerance from somewhat tolerant to sensitive.